Chemical Determination of Heavy Metals in Pb and Zn Concentrates of Trepça (Kosovo) and Correlations Coefficients Study Between Chemical Data (Rudarsko-geološko-naftni zbornik, 2017)
Kosovo ore deposits are located in the Trepça belt which extends for over 80 km. The concentrate produced by the flotation process of the Trepça metallurgical corporation contains a considerable quantity of valuable metals, such as Pb, Zn, Fe and minor accompanying metals such as Cd, Cu, As, Sb, Bi, Ag, Au, etc. The subject of this work was to assess the concentration of major and minor metals in lead and zinc concentrates of Trepça and to study the correlation coefficients between metals. Chemical determination of concentrates was performed by using atomic absorption spectroscopy (AAS). In the content on lead concentrate samples, the following were found: Pb>Fe>Zn> Ag> As>Sb>Cd. In the content of zinc concentrate, the following were found: Zn>Fe>Pb>Ag>As>Cd. The program “Statistica ver. 6.0” has been used for calculations of basic statistical parameters, relationships between data and cluster analysis of R-mode. R-mode cluster analysis on lead concentrate samples showed that Pb has the closest linkages with Fe and they form one branch of the dendogram. On the zinc concentrate samples, Zn has the closest linkages with Fe and they form one branch of the dendogram.